Peran Media Pembelajaran Digital Meningkatkan Kompetensi Pedagogik Guru SMPIT Takhassus Al-Qur’an Ashabiq - Putri, Ressy Resviati; Qomariyah, Siti; Aliyah, Lia; Rahmawati, Ai Siti; Sumarni, Leni (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The development of information technology in the era of Digital 4.0 has brought significant changes in the field of education, requiring teachers to transform from conventional methods to digital-based learning. This study aims to examine the role of digital learning media in enhancing teachers’ pedagogical competence in the Digital 4.0 era. The research employed a qualitative descriptive approach, using data collection techniques including observation, interviews, and documentation involving teachers and the school principal. The results indicate that the use of digital media such as Google Classroom, Canva, and YouTube Edu assists teachers in designing creative, interactive, and relevant learning aligned with the needs of 21st-century students. The use of digital media also improves teachers’ abilities in reflection and learning evaluation. However, the study identified several challenges, including limited internet connectivity, insufficient devices such as laptops, school policies prohibiting students from bringing mobile phones, and disparities in teachers’ digital skills. Overall, digital learning media play a crucial role in strengthening teachers’ pedagogical competence and supporting the implementation of innovative and adaptive learning in response to the challenges of the digital era.